Survey About the Use of Bacterial Inoculants in Brazil: Effects on Silage Quality and Animal Performance - Rabelo, Carlos H. S. [UNESP]; Mari, Lucas J.; Reis, Ricardo A. [UNESP]; DaSilva, T.; Santos, E. M. (Intech Europe, 2016)
Our objective was to report the effect of bacterial inoculants on silage quality and animal responses in Brazil. A survey of bacterial inoculants utilization in Brazil was made based on a total of 178 published articles assessing a widely varied crops (alfalfa, cabbage, cassava, corn, grass, high-moisture corn (HMC), high-moisture sorghum, millet, oat, orange bagasse, peanut forage, sorghum, soybean, stylosantes Campo Grande, sugarcane, and sunflower). Sugarcane and grass silages comprised 58.1% of the total crops investigated. Homolactic inoculation reduced dry matter (DM) losses in alfalfa silages, but not in corn, grass, HMC, and sorghum silages. Heterolactic inoculation enhanced the aerobic stability of corn and HMC silages. The use of heterofermentative lactic acid-bacteria (LAB) was more effective to improve fermentation of sugarcane silages compared to homofermentative LAB. Inoculation impaired the DM intake in cattle fed corn, grass, and sugarcane silages, but DM intake increased in sheep due to inoculation. In some cases, silage digestibility was affected by inoculation. Positive responses to inoculation occurred most often when the compatibility between the bacterial inoculant and crop was better understood (e. g., homolactic inoculation for grass silage and heterolactic inoculation for sugarcane silage). The performance of animals consuming inoculated silages has been investigated in Brazil only a few times, but the data suggest a greater impact of bacterial inoculants on DM intake and weight gain in cattle and sheep than that indicated in temperate conditions.
Keywords: aerobic stability; digestibility; fermentation; growth performance; lactic acid bacteria